2023
DOI: 10.3390/ani13111769
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory and Neuroprotective Effects of Caffeine in Neonate Animal Models

Abstract: Caffeine is widely used to improve neonatal health in animals with low vitality. Due to its pharmacokinetics and pharmacodynamics, caffeine stimulates the cardiorespiratory system by antagonism of adenosine receptors and alteration in Ca+2 ion channel activity. Moreover, the availability of intracellular Ca+2 also has positive inotropic effects by increasing heart contractibility and by having a possible positive effect on neonate vitality. Nonetheless, since neonatal enzymatic and tissular systems are immatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…However, in the present study, the decrease in Ca ++ might suggest an adaptative mechanism to hypoxia in response to caffeine and its stimulant cardiovascular effects. Caffeine facilitates intracellular Ca ++ mobilization to improve muscular performance and cardiac activity [60]. In vitro studies have shown that caffeine has benefits on cardiac contractility [61], possibly improving oxygen transportation to other cellular tissues in hypoxic piglets.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the present study, the decrease in Ca ++ might suggest an adaptative mechanism to hypoxia in response to caffeine and its stimulant cardiovascular effects. Caffeine facilitates intracellular Ca ++ mobilization to improve muscular performance and cardiac activity [60]. In vitro studies have shown that caffeine has benefits on cardiac contractility [61], possibly improving oxygen transportation to other cellular tissues in hypoxic piglets.…”
Section: Discussionmentioning
confidence: 99%
“…However, low-vitality newborns present an abnormal behavioral repertoire that impedes colostrum intake and other behaviors that prevent hypothermia [ 95 ]. In this regard, Murray and Leslie [ 97 ] mention that low-vitality neonates cannot ingest colostrum for energy uptake and thermoregulation due to a lack of vigor and energy to stand up and get close to the udder.…”
Section: Intrinsic Factors Affecting the Temperature In The Newborn B...mentioning
confidence: 99%
“…Therefore, calves with low vitality cannot produce heat as efficiently as a normal newborn, and the effect of hypothermia on the delayed response to ingesting colostrum increases neonatal energy depletion and the risk of mortality [ 97 ]. Although some conclusions could be inferred, such as the importance of evaluating the rectal temperature of newborns, some authors have referred to the importance of evaluating physiological data with modified APGAR scores [ 95 ], particularly in water buffalo, in whom vitality assessment at birth is limited.…”
Section: Intrinsic Factors Affecting the Temperature In The Newborn B...mentioning
confidence: 99%
See 1 more Smart Citation